FREQUENCY AND GRADING OF INTRAVENTRICULAR HEMORRHAGE IN PRETERM BABIES ADMITTED IN NATIONAL INSTITUTE OF CHILD HEALTH, KARACHI, PAKISTAN - Kumar, Deepak; Khan, Mashal; Sheikh, Mehmood; Muhammad Hanif, (Journal of Postgraduate Medical Institute, 2023)
Objective: To report the frequency of IVH in preterm neonates and IVH grading on cranial ultrasound. Methodology: This prospective cross-sectional study was carried out at NICH. All preterm infants of either gender were consecutively enrolled. Detailed history of the infant regarding the clinical examination and socio-demographic characteristics of the infants were noted. IVH was observed in all preterm neonates, and all infants were categorized according to the Papile grading. Results: Of 144 neonates, the mean age was 2.34 ±0.97 days. There were 93 (64.6%) males and 51 (35.4%) females. IVH was observed in 144 (37.6%) neonates. A significant mean difference of age (p: <0.001), gestational age (p: <0.001), birth weight (p: <0.001), APGAR score at 1 min (p; <0.001), APGAR score at 5 min (p: <0.001) was observed in between IVH and non IVH neonates. Furthermore, a significant association of place of admission (p: <0.001), mode of delivery (p: 0.038), need of invasive/non-invasive ventilator (p: 0.002), and preterm status (p: <0.001) was observed with IVH. IVH grade I was observed in 75 (52.1%), grade II in 45 (31.3%), grade III in 18 (12.5%), and grade IV in 6 (4.2%) neonates. Conclusion: A notably higher number of preterm neonates had IVH. While grade I was most common, a majority exhibited severe grades (III and IV). Extremely early preterm births carried increased risk of spontaneous delivery and greater reliance on invasive/non-invasive ventilator support.